2019
DOI: 10.15421/021955
|View full text |Cite
|
Sign up to set email alerts
|

Impact of essential oil from plants on migratory activity of Sitophilus granarius and Tenebrio molitor

Abstract: Measures against pests should be performed in the context of integrated management of agricultural crops and complex control of pests. Therefore, use of ecologically safe approaches is the best option. Essential oils of plants can make an impact on the main metabolic, biochemical, physiological and behavioural functions of insects. We evaluated the effect of 18 essential oils and 18 dried plants on migratory activity of Sitophilus granarius (Linnaeus, 1758) and Tenebrio molitor Linnaeus, 1758 in conditions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 84 publications
1
5
0
Order By: Relevance
“…Previous studies have demonstrated that Eucalyptus globulus EO acts as a repellent for adult mealworms [15] but not for larvae [16]. However, dried and ground leaves of this eucalyptus were found to be repellent to larvae.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have demonstrated that Eucalyptus globulus EO acts as a repellent for adult mealworms [15] but not for larvae [16]. However, dried and ground leaves of this eucalyptus were found to be repellent to larvae.…”
Section: Discussionmentioning
confidence: 81%
“…The broad range of chemical interactions between insects and the environment is constantly studied, and a relatively full data base on pheromones of insects is available on the internet (www.pherobase.com). Our studies indicate that agriculturally significant insects can react to chemical compounds and their mixture in fooder (Brygadyrenko & Nazimov 2015;Martynov et al, 2019aMartynov et al, , 2019b, as well as chemically synthesized substances introduced to their environment (Titov & Brygadyrenko, 2021). Influence of household chemicals to which insects inside or near households are daily subjected has been studied fragmentarilly (Nehrii & Brygadyrenko, 2022), and such studies have not been conducted on Turkestan cockroach until now.…”
Section: Introductionmentioning
confidence: 94%
“…Weevils of the Sitophilus genus are significant as a pest of barns (Martynov et al, 2019;Titov & Brygadyrenko, 2021). Our previous studies revealed that rice weevils Sitophilus oryzae (Linnaeus, 1763) are able to accumulate and spread dissociative forms of mycobacteria.…”
Section: Introductionmentioning
confidence: 99%